Cauda equina syndrome successfully treated with microdiscectomy and methylprednisolone therapy: A case report - Henderson, Alhoi Hendry; Ibrahim, Sabri (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Cauda equina syndrome (CES) caused by lumbar disc herniation is a rare neurosurgical emergency in young adults that requires immediate decompression. A surgical delay over 48 hours may result in irreversible ramifications, underscoring a crucial timeframe for managing this condition. We presented a 26-year-old man with lower limb weakness persisting for one week, accompanied with exacerbating bowel and bladder issues after massage. The patient had a history of low back pain and tingling sensations radiating to the left leg over the past year. His physical examination showed right motor strength of 5/4 and left motor strength of 5/3, with weakened bowel peristalsis, loose anal sphincter and saddle anaesthesia. A spinal MRI revealed protruded discs extending to the intervertebral levels of L4-L5 and L5-S1, implicating herniated discs as the likely cause of CES. He underwent a microdiscectomy with a posterior approach, and intravenous methylprednisolone was administered before the procedure. The next surgery demonstrated enhancements in motor strength, bowel and bladder function, and it also reduced pain. He was discharged with persistent tingling sensations in his both legs. We concluded that CES represents a critical neurosurgical emergency, which is diagnosed through clinical symptoms and neuroimaging. Rapid decompression and intravenous administration of methylprednisolone are associated with better prognosis.